Evaluation of the accuracy of satellite-based rainfed wheat yield dataset over an area with complex geography. (May 2023) - Eini, Mohammad Reza; Motehayeri, S.Mohammad S.; Rahmati, Akbar; Piniewski, Mikołaj
Abstract: Global gridded datasets have a potential of being a reliable resource for filling gaps in observed data in global and regional studies. Global gridded cropping system datasets are useful in various fields, such as crop and hydrological simulations. They could serve as a source alternative to observed datasets. This study evaluates data on rainfed wheat yield derived from a satellite-based Global Dataset of Historical Yields (GDHY) over Iran from the years 1983–2016 (in this period, the average rainfed wheat yield over Iran was 0.86 tons/ha). The process of development of this dataset employed satellite products, solar radiation, harvested area, crop calendar, and production share by cropping season. Our evaluations were conducted at the country scale, province scale, and in reference to different climates based on the Köppen-Geiger climate classification. The index of agreement over Iran is approximately 0.79, and according to percentage bias, GDHY has a 1.6% error over Iran. The dataset was reliable at the sub-national level, over the western parts, and particularly in the mountainous region. In reference to the root mean square error (tons/ha), it showed the lowest performance in the humid part of Iran (Mazandaran, Gilan, and Golestan provinces). Drought analysis showed that the reference crop yield dataset over the study area is more consistent with SPI-12, although GDHY agrees with SPI-3. In contrast to drier years in recent years, the crop yield has increased. This positive trend can be justified by increasing the rate of fertilizer applications, better grazing, an overall improvement in farming technologies, and better farm management at the country scale. In conclusion, GDHY can be used at the national scale for different analyses or modeling, but it is inaccurate at the sub-national level. Graphical abstract: Image 1 Highlights: The first assessment of a global crop yield dataset (GDHY) at sub-national level. Rainfed wheat yield is evaluated over Iran and sub-national levels (1983–2016). GDHY has generally recorded higher yields. The reference crop yield dataset over Iran is more consistent with SPI-12. The used dataset has high accuracy over western parts of Iran, particularly in the mountainous region.